STRATEGI GEMBALA DALAM PEMANFAATAN AKTIVITAS JEMAAT MENUJU PERTUMBUHAN ROHANI - Andarias Tandi Barana; Wahyu Sinta Delfia; Elisabet Tarigas (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2020)
The purpose of this study is to find the causative factors and problems of the GKSI Filadelfia Buntu Barana congregation that are less experiencing spiritual growth. Than directed through the strategy of pastors or servants of God to increase formation of the congregation in the midst of many of their busy actifities that prioritize work rather than worship or followship in church on Sundays. The methods used in this study are: First, the library research method is a study of books end literature relating to this research as a theorectical reference. Second, the method of field research is research conducted directly to the object of research by observation or direct observation in the field, and interviews. The conclusions of this study are: first, the spiritual growth hampered by the GKSI Buntu Barana congregation because there is not yet real repentance for some congregations, second, there are obstacles that hinder the spiritual growth of the GKSI Buntu Barana congregation, including the lack of community and social environment that does not support spiritual growth of the church. Third, some effective strategies in increasing the spiritual quality of congregants are by engaging in their busy activities by getting involved in their busy work, outside of worship hours as Christians should: Suday Services, Hausehold Services, School Services Sunday, Youth Services, Church prayer Services, and visits if they are at home. In addition we as servents of Gad often provide young people with a variety of creativity.